Contributions of Zvi Griliches - James Joseph Heckman (Institute for the Study of Labor (IZA), 2006)
In this article, I summarize Griliches' contributions to economics and to applied econometrics.
Keywords: B31; D24; O33; 330; social rate of return; growth; productivity improvement; Technischer Fortschritt; Produktivität; Rendite; Hedonischer Preis; Publikationsanalyse